A savage war a military history of the Civil War - Murray, Williamson; Hsieh, Wayne Wei-siang (Princeton University Press, 2016)
The Civil War represented a momentous change in the character of war. It combined the projection of military might across a continent on a scale never before seen with an unprecedented mass mobilization of peoples. A military history of breathtaking sweep and scope, A Savage War reveals how the Civil War ushered in the age of modern warfare.